Proses Berpikir Siswa dari Situasi ke Matematika Formal Melalui Pendekatan RME dalam Penyajian Diagram Lingkaran - Mey Liasta Trihastina Br Tarigan; Sugiman (Mandalika Mathematics and Educations Journal, 2026)
This study aims to describe the students’ thinking process in learning data presentation using pie charts through the Realistic Mathematics Education (RME) approach. The method used is Design Research with two seventh-grade junior high school students in Yogyakarta as subjects. Learning is designed in stages from real-life extracurricular contexts to formal mathematical representations using doll props, conversion from fractions to percentages, calculation of angle sizes, and presentation of pie charts. The results show that the RME approach effectively enhances students' conceptual understanding gradually and encourages active involvement in modeling and independently presenting data. Although there were some technical misconceptions, teacher guidance successfully helped students overcome these difficulties. This study reinforces the importance of contextual and representational learning in improving mathematical literacy, especially skills in presenting and interpreting data using pie charts. Keywords: Data presentation 1; mathematical literacy 2; pie chart 3; Realistic Mathematics Education 4; students' thinking process 5.